Synthesis of novel beta-substituted alpha,beta-dehydroamino acid derivatives - Ferreira, Paula M. T. (2000)
beta-Substituted alpha,beta-dehydroamino acids are synthesised in high yields by a Michael addition of heterocyclic nucleophiles to the methyl esters of N-tert-butyloxycarbonyl,N-(4-toluenesulfonyl)dehydroamino acids, followed by a base-induced elimination of the 4-toluenesulfonyl group with regeneration of the alpha,beta-double bond.